Hematoma intramural del duodeno - Campos Pierri, Néstor; Revetria Invernizzi, Ricardo; Acosta y Lara, Armando (Cirugía del Uruguay, 1979)
Intramural Duodenum Hematoma Report on 2 cases of intramural duodenum post-traumatic hematomas. There follows a discussion about their etiopathogenesis, clinical aspects, radiology and treatment.